Pengaruh Tingkat Pendidikan dan Pengalaman Kerja terhadap Kinerja Karyawan Pada PTHasura Mitra Gemilang Tangerang - Siti Riana Tantri; Berlianingsih Kusumawati (Indonesian Journal of Economics Application (IJEA), 2021)
This study aims to analyze the effect of education level and work experience on employee performance at PT Hasura Mitra Gemilang Tangerang. This research design uses quantitative associative methods and data collection techniques in library research and field research. The data analysis technique used in this study uses multiple linear regression. The sampling method uses non-probability sampling techniques. The Research sample amounted to 83 Respondents. The study results prove that the level of education has a positive and significant effect on employee performance.